2019
DOI: 10.3390/su11133719
|View full text |Cite
|
Sign up to set email alerts
|

Application of Roadway Backfill Mining in Water-Conservation Coal Mining: A Case Study in Northern Shaanxi, China

Abstract: The mining induced subsidence and strata deformation are likely to affect the stability of the aquiclude, resulting in loss of water resources in the mining area. In order to reduce the disturbance of coal mining to the overlying strata and to preserve the water resources in the coal mining area, the roadway backfill mining (RBM) method was trialed in Yuyang coal mine in Northern Shaanxi, China. Based on pressure arch theory and ultimate strength theory, a mechanical model was developed to analyze the stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…e accumulation of coal gangues has caused a series of environmental problems [1][2][3], such as land occupation, water pollution, and air pollution after spontaneous combustion [4][5][6][7]. In addition, coal mining can also cause the fracture of key strata [8][9][10][11], resulting in the loss of groundwater resources [12][13][14] and surface subsidence [15,16]. Solid backfill mining is an environmental coal mining technology, in which coal gangue is used as the main filling body to replace the underground coal resources [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…e accumulation of coal gangues has caused a series of environmental problems [1][2][3], such as land occupation, water pollution, and air pollution after spontaneous combustion [4][5][6][7]. In addition, coal mining can also cause the fracture of key strata [8][9][10][11], resulting in the loss of groundwater resources [12][13][14] and surface subsidence [15,16]. Solid backfill mining is an environmental coal mining technology, in which coal gangue is used as the main filling body to replace the underground coal resources [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Backfill coal mining technology is an effective method to improve the utilization of coal resources and control surface subsidence. It has been widely used in China and has become one of the main means of green coal mining [1][2][3][4][5][6][7][8]. e stability of the backfill is an important factor to prevent the instability of the goaf and the subsidence of the ground surface [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Through studying the damage law of overlying strata in roadway backfill mining, Sun Q et al [38] found that the filling body could successfully support the overlying load, and the strata remains stable after mining. Yu YH et al [39] analyzed the stability of coal pillars in roadway backfill mining, and proposed subsidence equations of every stratum in mining. The above-mentioned various coal mining and backfilling methods are similar to the CECB method in the panel plan and mining and backfilling sequences.…”
Section: Introductionmentioning
confidence: 99%